The structure of the forensic characteristics of offences under Article 200 of the Criminal Code of Ukraine - L. Ye. Barash (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to determining the structure of the forensic characteristics of crimes under Article 200 of the Criminal Code of Ukraine “Illegal actions with the documents for transfer, payment cards and other means of access to bank accounts, electronic money, equipment for their production”. The theoretical foundations of developing forensic characteristics of a particular type of crime have been analysed and the grounds for forming its structure have been highlighted. These grounds include criminal law elements of a crime, a list of circumstances to be proved in criminal proceedings, and elements of the mechanism of committing illegal actions with payment instruments. Significant elements for the forensic methodology of the criminal law characteristics of the crime under investigation are its subject matter, method of commission and subjective features. Among the elements of the subject matter of proof, the most important are also the object, method and identity of the offender, as well as the time, place and other circumstances of the crime.